Alfu Laylah wa-Laylah bayn al-Ḥaḍārah al-‘Arabīyah wa-al-Ūrūbīyah - Asmara, Hilda Dimyati; Syahid, Ahmad Habibi (Universitas Negeri Jakarta, 2022)
Many Muslims today are ignorant of their history and glory in the past. They are unaware of their ancestors, who were role models and leaders of the world culturally and scientifically. On the other hand, the tale of “One Thousand and One Nights” achieved tremendous popularity worldwide. Hence, the writers wanted to highlight the value and the influential role he played in human societies. In addition, Night is pure spring water with its freshwater, the European novel tree. In some instances, many books were produced by French and German authors. The nature of this study necessitated taking advantage of the descriptive method, which defies facts, in addition to studying the phenomenon as a result of influencing the construction of the literary work, what the writer did for this tributary that he drew from others, and how he employed it in his literary output. Arab and European literature is influenced by each other, as it appears in the imaginary drawings of Europeans inspired by the story of the Thousand and One Nights. In contrast, the Arabs were influenced intellectually, taking into account their cultural and civilizational specificity.